Research and Medicinal Potential of the genus Cestrum (Solanaceae) – A Review - Begum, A. Sajeli; Goyal, Madhur (Pharmacognosy Reviews)
The genus Cestrum belonging to Solanaceae family comprises about 300 species. Cestrum, which was mainly distributed in South America ranges from Southern Florida and Northern Mexico to Chile is now distributed all over the world as an ornamental plant. The genus is rich in saponins and most of the species exhibit toxicity supporting their use as potential insecticide, herbicide, molluscicide, antimicrobial agent and anticancer agent. A characteristic species of this genus, Cestrum diurnum is known for its calcinogenic potential, which can be used as a source of vitamin D in poultry. The present review explores the distribution, chemical composition, pharmacological activity and traditional uses of different species of genus Cestrum.
Keywords: Cestrum; Solanaceae; Cestrum diurnum; calcinogenesis; vitamin D3; saponins